2001
DOI: 10.1073/pnas.041610998
|View full text |Cite
|
Sign up to set email alerts
|

A second-generation vaccine protects against the psychoactive effects of cocaine

Abstract: The effects of immunization with the second-generation cocaine immunoconjugate GND-keyhole limpet hemocyanin (KLH) or with the anti-cocaine mAb GNC92H2 were assessed in a model of acute cocaine-induced locomotor activity. After i.p. administration of cocaine⅐HCl (15 mg͞kg), rats were tested in photocell cages, and stereotypy was rated to determine preimmunization drug response (baseline). Experimental animals were subjected to an immunization protocol with GND-KLH or treated with the mAb GNC92H2. Rats were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…E-mail address of the corresponding author: kdjanda@scripps.edu nopharmacological approach, our laboratory [6][7][8][9] and others, 10,11 have demonstrated that anti-cocaine antibodies can prevent the psychomotor effects attributable to cocaine. Passive immunization of rats with monoclonal antibody (mAb) GNC92H2 impeded the entry of cocaine into the brain and thus led to a significant decrease in stereotypic behavior.…”
Section: Introductionmentioning
confidence: 96%
“…E-mail address of the corresponding author: kdjanda@scripps.edu nopharmacological approach, our laboratory [6][7][8][9] and others, 10,11 have demonstrated that anti-cocaine antibodies can prevent the psychomotor effects attributable to cocaine. Passive immunization of rats with monoclonal antibody (mAb) GNC92H2 impeded the entry of cocaine into the brain and thus led to a significant decrease in stereotypic behavior.…”
Section: Introductionmentioning
confidence: 96%
“…The majority of work in this area has been conducted with vaccines directed against cocaine [24][25][26] and nicotine [27][28][29][30][31]. In addition, vaccines for heroin [32], phencyclidine [33], methamphetamine [34] have also been developed.…”
Section: Introductionmentioning
confidence: 98%
“…The studies have focused on the ability of mAb to affect drug discrimination and relapse to drug use. In rats, passive immunization reduced reinforcing effects, and reinstatement of cocaine self-administration after low-dose cocaine (Carrera et al, 2000;Carrera et al, 2001). The recombinant of a humanized anti-cocaine mAb was reported with a modest KD value for cocaine of about 200 nM (Redwan et al, 2003).…”
mentioning
confidence: 97%
“…Drug vaccines induce drug-specific antibodies in the bloodstream, which bind to the drug of abuse and prevent it from entering the brain. Several studies demonstrated that immunization against cocaine can reduce drug intake and drug-seeking behavior in rats and mice (Carrera et al, 1995;Kantak et al, 2000;Carrera et al, 2001). Vaccines for cocaine and nicotine can generally offer long-term protection with minimal treatment compliance.…”
mentioning
confidence: 98%